2020
DOI: 10.1002/bmc.4871
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pressure on the characteristics of supercritical carbon dioxide extracts from Calamintha nepeta subsp. nepeta

Abstract: Chemists and industrialists are continuously attempting to develop greener and more environmentally benign chemical processes to extract essential oils and bioactive metabolites of high purity, finding various applications in cosmetics, detergents, nutraceuticals and pharmaceuticals. An increase preferenced for natural products over synthetic ones has made supercritical fluid technology a primary alternative for the generation of high‐value bioactive ingredients. This effective technique requires only moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However ß‐ caryophyllene (24.65%) was detected at a higher percentage in G. foetida collected from the northwestern part of Morocco. It is noteworthy that this variability can be related to the geographical origin, environmental factors, genetic variation and the harvest period (Debbabi et al, 2020; Majdoub et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…However ß‐ caryophyllene (24.65%) was detected at a higher percentage in G. foetida collected from the northwestern part of Morocco. It is noteworthy that this variability can be related to the geographical origin, environmental factors, genetic variation and the harvest period (Debbabi et al, 2020; Majdoub et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could promote the activation of enzymes, changes in the metabolic substrates for aroma compounds (mainly amino acids and fatty acids), and/or greater retention of the typical aroma compounds during processing due to its low impact on the structure of these small‐molecule compounds. However, at higher pressures, degradation reactions may occur (Amaral, Silva, Cavalcanti, et al., 2018; Debbabi et al., 2020). In these cases, it is advisable to recover the volatile compounds in the exit system and re‐incorporate them into the products (Amaral, Silva, Cavalcanti, et al., 2018).…”
Section: Quality Parameters Of Food Products Processed By Sc‐co2 Tech...mentioning
confidence: 99%
“…Debbabi et al have reported a change in extraction yield of bioactive components from Calamintha nepeta subsp. nepeta from 0.73 to 1.21 wt% at 90 and 300 bar, respectively [57]. On the other hand, lower pressures of parsley fruit extracts comprised mainly of the phenylpropene, apiole, were reported to have stronger antibacterial effects [58].…”
Section: Supercritical Fluid Extraction (Sfe)mentioning
confidence: 99%